2020
DOI: 10.1093/jn/nxaa081
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Hemp Seeds More Effectively Attenuate Disorders in Genetically Obese Rats than Their Lipid Fraction

Abstract: Background Hemp seeds are rich in PUFAs and other bioactives that can attenuate the development of obesity-related disorders; however, the extent to which their lipid fraction is responsible for this effect is unknown. Objective We hypothesized that hemp seed or hemp oil supplementation can attenuate genetically determined disorders and that the former are more effective in doing so. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 49 publications
7
21
1
Order By: Relevance
“…Another important factor in the modulation of the lipid profile might have been the rat phenotype. In our previous study on obese Zucker rats, a reduction of the plasma HDL cholesterol level after dietary supplementation with hemp seed oil was also observed [35]. Interestingly, changes in the blood lipid profile were not the case in healthy animals, which confirms our hypothesis that the health state of rats is an important factor in the modulation of lipid metabolism by the tested oils.…”
Section: Discussionsupporting
confidence: 82%
“…Another important factor in the modulation of the lipid profile might have been the rat phenotype. In our previous study on obese Zucker rats, a reduction of the plasma HDL cholesterol level after dietary supplementation with hemp seed oil was also observed [35]. Interestingly, changes in the blood lipid profile were not the case in healthy animals, which confirms our hypothesis that the health state of rats is an important factor in the modulation of lipid metabolism by the tested oils.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the decreased plasma uric acid by the seeds in the present study can be considered beneficial for the body, especially when looking at its role in the development of gout. Support of this supposition can be found in the study by Opyd et al [9], who showed that dietary supplementation with hemp seeds improved the antioxidant status of the liver in Zucker rats by increasing glutathione levels and decreasing a marker of lipid peroxidation. This means that a considerable decrease in the plasma antioxidant capacity and uric acid level does not automatically exclude benefits coming from hemp seed supplementation to the organ's antioxidant defense system.…”
Section: Discussionmentioning
confidence: 83%
“…An interesting and relatively less known source of fatty acids is the seeds of industrial hemp ( Cannabis sativa L.), as they contain a large amount of PUFAs, including linoleic and α-linolenic acids (approx. 53% and 18% of total fatty acids) and some small amount of other fatty acids that are uncommon in vegetable oils, such as γ-linolenic acid [ 8 , 9 ]. The oil from hemp seeds is characterized as having an optimal ratio of n-3 to n-6 PUFAs (1:3), so important for the adequate functioning of the cardiovascular system; however, hemp oil contains trace amounts of trans fatty acids, which are generally thought to raise the risk of atherosclerosis by inhibiting the synthesis of other PUFAs in arterial cells [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations